DATA-DRIVEN DECISION MAKING: FINANCIAL AND RISK ANALYSIS ON EQUIPMENT PROCUREMENT AT PT ABC - Rizki Firdaus, Ahmad
This study explores strategic financial management solutions for PT ABC during the COVID-19 pandemic, with a focus on the procurement of vital airport equipment. It examines the feasibility of acquiring essential heavy equipment such as ARFF vehicles, X-ray machines, ambulances, and narcotics & explosives detectors amidst financial challenges. Employing financial models like predictive data estimation, Net Present Value (NPV) analysis, owner estimates, and Monte Carlo simulations, this research evaluates the probabilities and risk distributions associated with various procurement strategies. The objective of the study is to determine the most economical vendors and procurement methods, using owner estimates as a negotiation tool. Risk evaluation is carried out through Monte Carlo simulations, providing insights into the likelihood and impact of risks related to procurement. In conclusion, this research identifies Vendor A for ARFF vehicles, Vendor D for X-ray machines, Vendor E for ambulances, and Vendor G for narcotics & explosives detectors as the most cost-effective options. Leasing with a 3-year period emerges as the most feasible financial option, in accordance with PT ABC’s internal regulations. Utilizing owner’s estimates for negotiation leads to lower procurement costs with a cost difference ranging from 24.66% to 40.43%. Monte Carlo simulations indicate a higher risk associated with purchasing than leasing. This research enhances the effectiveness of PT ABC's heavy equipment procurement in strategic decision-making by integrating various financial and risk analyses.